Βιβλιοκρισία του: A. KALDELLIS - S. EFTHYMIADIS, Prosopography of byzantine Lesbos 284-1355 A. D. A Contribution to the social History of the Byzantine province [Verlag der Oesterreichischen Akademie der Wissenschaften], Wien 2010 - ΛΟΥΪΖΙΔΗΣ Κίμων Χ. (Byzantina Symmeikta, 2011)
Βιβλιοκρισία του έργου:A. Kaldellis-S. Efthymiadis, Prosopography of byzantine Lesbos 284-1355 A. D. A Contribution to the social History of the Byzantine Province, Verlag der Österreichischen Akademie der Wissenschaften, Wien 2010, σ. 204 + 6 χάρτες (ISBN 978 – 3 – 7001 – 4005 – 4)